Gamma-oryzanol as a potential modulator of oxidative stress and inflammation via PPAR-y in adipose tissue: a hypothetical therapeutic for cytokine storm in COVID-19? - Francisqueti-Ferron, Fabiane Valentini [UNESP] (2021)
The literature has reported a higher prevalence of negative clinical outcomes due to Coronavirus disease 19 (COVID-19) in obese individuals. This can be explained by the cytokine storm, result from the cytokine production from both obesity and viral infection. Gamma-oryzanol (γOz) is a compound with anti-inflammatory and antioxidant activities. However, little is known about the γOz action as a possible agonist of peroxisome proliferator-activated receptor gamma (PPAR-γ). The aim of this study was to test the hypothesis that γOz attenuates the cytokine storm by stimulating PPAR-γ in the adipose tissue. Methods: Male Wistar rats were randomly divided into three experimental groups and fed ad libitum for 30 weeks with control diet (C, n = 6), high sugar-fat diet (HSF, n = 6) or high sugar-fat diet + γOz (HSF + γOz, n = 6). HSF groups also received water + sucrose (25%). The γOz dose was 0.5% in the chow. Evaluation in animals included caloric intake, body weight, adiposity index, plasma triglycerides, and HOMA-IR. In adipose tissue was evaluated: PPAR-γ gene and protein expression, inflammatory and oxidative stress parameters, and histological analysis. Results: Adipose tissue dysfunction was observed in HSF group, which presented remarkable PPAR-γ underexpression and increased levels of cytokines, other inflammatory markers and oxidative stress. The γOz treatment prevented adipose tissue dysfunction and promoted PPAR-γ overexpression. Conclusion: Natural compounds as γOz can be considered a coadjutant therapy to prevent the cytokine storm in COVID-19 patients with obesity conditions.